Phenol solutions treatment by using hydrophobized track-etched membranes - Yeszhanov, A.B.; Dosmagambetova, S.S. (KSU Publ., 2020)
Phenols are one of the most common surface water pollution. The discharge of phenolic waters into water bodies and streams sharply degrade their general sanitary condition, since these compounds have a toxic effect, and phenols can intensively absorb oxygen dissolved in water, which negatively affects the life of organisms in water bodies. Therefore, water treatment of phenols is an important environmental problem. In this study, the hydrophobic polyethylene terephthalate track-etched membranes (PET TeMs) were tested in water treatment from phenol by direct contact membrane distillation (DCMD). Hydrophobic PET TeMs were obtained by UV-graft polymerization of styrene, triethoxyvinylsilane with the addition of vinylimidazole (VIM), as well as by coating with fluorine-containing silanes. Scanning electron microscopy (SEM), Fouriertransform infrared (FTIR) spectroscopy and liquid entry pressure (LEP) analysis were used for membrane characterization. The contact angle after modification of PET TeMs was reached more than 130°. The efficiency of water purification from phenol was evaluated by water-flux measurements and fluorimetric method. The phenols solution was used at a concentration of 0.5, 1 and 2 g/l. The largest permeate flux of hydrophobized membranes was 1.1 kg/ m2·h.
Фенол ерітінділерін гидрофобты тректі мембраналармен тазарту
Очистка растворов фенола гидрофобными трековыми мембранам
Keywords: phenol; water treatment; direct contact membrane distillation; UV-induced graft polymerization; styrene; triethoxyvinylsilane; fluorine-containing silanes; track-etched membranes